Implications of dietary soybean meal replacement with corn gluten meal on growth performance, antioxidant activities, hepatopancreatic histopathology, and intestinal flora of juvenile Pacific shrimp (Litopenaeus vannamei) - Mpwaga Alatwinusa Yohana; Gyan Watson Ray; Qihui Yang; Beiping Tan; Shuyan Chi; Huaxing Lin; Minling Mao; Yuanming Yi (Aquaculture Reports, 2023)
This study aimed to investigate the potential of replacing soybean meal (SBM) with corn gluten meal (CGM) in the diet of Pacific white shrimp (Litopaeneaus vannamei). The study examined the effects of a dietary soybean meal replacement on growth, biochemical indices, antioxidant activities, histology, and intestinal flora. A total of 840 juvenile Pacific shrimp were fed seven diets containing different levels of CGM, ranging from diet 1 (diet1) 0% (control), diet2 (3%), diet3 (7%), diet4 (9%), diet5 (11.8%), diet6 (12.7%), and diet 7 (14.4%). The experiment was conducted over 56 days, with three replicate of each group (initial mean weight = 0.13 0.00 g). The results showed that dietary CGM significantly increased final body weight, average weight gain, and specific growth rate. However, the inclusion of dietary CGM decreased with higher levels. The feed conversion ratio of diets 2 and 3 was considerably lower than that of the control group. The activities of alkaline phosphatase and acid phosphatase increased significantly with the feeding of CGM, while the levels of alanine aminotransferase and aspartate aminotransferase decreased significantly. The histology of the hepatopancreas showed an evident epithelial tubule (E, B, R, and F), and the number of intact epithelial cells increased considerably with the increasing inclusion of CGM (P < 0.05). The intestinal flora in the shrimp intestine responded favorably to the replacement of SBM with CGM in the dietary CGM treatment groups, including a number of beneficial bacteria such as Bacteroidetes and Firmicutes. Moreover, with rising CGM levels, diversity indices and richness estimates rose. The regression model with a broken line was found to describing the relationship between the growth rate and the optimal level of CGM required. The results showed that a CGM dose of 3.31% was the most effective for achieving optimal growth performance in juvenile L. vannamei.